THE JUSTIFICATION OF MAQASID AL-SHARI’AH THROUGH THE DOCTRINES OF USUL AL-FIQH AND QAWA’ID AL-FIQHIYYAH: A STUDY ON SECURITIZATION PROCESS - Mohd Shahid bin Mohd Noh; Mohammad Taqiuddin bin Mohamad (Journal of Islamic, Social, Economics and Development, 2018)
Maqasid al-SharÄ«ah is a divine knowledge that had been embodied in the commands of syaraâ€™ through the revelation of Al-Quran and hadith. The strong relationship between this science with the doctrines usÅ«l al-fiqh (UF) and qawÄâ€™id al-fiqhiyyah (QF) could not be denied as demonstrated by our traditional scholar in their books. Hence, the understanding of this knowledge also might be achieved through the doctrines and maxims. This paper attempts to demystify how the securitization process complied with maqasid al-shariâ€™ah. The primary data of this study is collected through several interviews with the experts consisted of academicians, scholars and practitioners in the industry. This study finds that asset securitization despite deemed as a new innovation in Islamic finance, is a process which fulfills the requirements of maqasid al-shariâ€™ah (MS) by adopting the concept of al-rahn or pledge in islamic transactions law, acts as a mean for wealth expansion aligned with hifz al-mal concept, protecting the right and ownership of the asset and adhered to the requirements in Islamic asset securitsation. Although the process is seemed new and complicated in muâ€™amalat law, it however fulfils the requirements of MS and considered as shariâ€™ah compliance process that adopted broadly in current market practices.